BEYOND THE COLONIAL NOVEL: THE LAST NOVELS OF LAURENS VAN DER POST - Lloyd, D. W. (Literature and theology, 1999)
This article argues that while Van der Post accepts the narrative structures of the colonial quest-romance in A Story Like the Wind and A Far-Off Place, he transforms and goes beyond the trope by rejecting colonial perceptions and infusing his books with Jungian intimations of reality. His protagonists achieve a wholeness of being that allows them to move beyond Manichean polarities and transcend the blinkered sensibilities of their literary forebears. They are not only liberated from the ideologies of colonialism, racial dominance and Markism, but also from an epistemological vision that has constituted contemporary reality in terms which deprive the human spirit of its full potentials.